2013
DOI: 10.1007/s13337-013-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

First report of Chilli veinal mottle virus in Naga chilli (Capsicum chinense) in Meghalaya, India

Abstract: The present study confirms the occurrence of Chilli veinal mottle virus (ChiVMV) under the genus Potyvirus in Naga chilli (Capsicum chinense) in Meghalaya based on mechanical transmission assay, transmission electron microscopy, RT-PCR and sequence analysis. This is the first record of Chivmv in Naga chilli in North-East India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…Chilli is reported to be affected by more than 30 economically important viruses by causing 15–50% of yield losses in chilli cultivation 2 , 3 . It includes Cucumber mosaic virus 4 , Chilli leaf curl virus 5 , Tomato spotted wilt virus 6 , Groundnut bud necrosis virus 7 , Capsicum chlorosis virus 8 , Tobacco mosaic virus 9 , Potato virus Y 6 , Tomato leaf curl New Delhi virus 10 and Chilli veinal mottle virus 11 . Among them the cucumo and tospoviruses are the most predominant viruses reported to infect almost all the vegetables crops and pose serious threat to chilli production 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Chilli is reported to be affected by more than 30 economically important viruses by causing 15–50% of yield losses in chilli cultivation 2 , 3 . It includes Cucumber mosaic virus 4 , Chilli leaf curl virus 5 , Tomato spotted wilt virus 6 , Groundnut bud necrosis virus 7 , Capsicum chlorosis virus 8 , Tobacco mosaic virus 9 , Potato virus Y 6 , Tomato leaf curl New Delhi virus 10 and Chilli veinal mottle virus 11 . Among them the cucumo and tospoviruses are the most predominant viruses reported to infect almost all the vegetables crops and pose serious threat to chilli production 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Biotic constraints particularly symptoms akin to viral infection has long been recorded as a major hurdle to the successful production of these chillies in the region. High incidence of viral infection as recorded through visual observations of symptoms and recent report of ChiVMV infection on Naga chilli from Meghalaya indicated the possibility of its association with chilli decline in the NE region (Banerjee et al 2014). NE region being contagious to the Eastern Asian region provided a strong base for the possible prevalence of pathogenically and genetically diverse ChiVMV isolates.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the sequencing of a genomic fragment, association of chilli leaf curl virus (CLCuV) with Capsicum chinense was also reported (Adluri et al 2016). Recently, first authentic molecular evidence for the infection of Chilli veinal mottle virus (ChiVMV) in Capsicum chinense from low to moderate temperature geographical areas of NE India was provided (Banerjee et al 2014). ChiVMV was suspected to be responsible in bringing havoc in the chilli plantations in Manipur also, where similar low to moderate temperature conditions prevails.…”
Section: Introductionmentioning
confidence: 99%
“…Reports are available on the survey of viral disease incidence in Bhutjolokia from Assam based on symptomatology, transmission, host range and serological assays (Baruah et al, 2016;Talukdar et al, 2015Talukdar et al, , 2017. Molecular method have also been used for the detection and confirmation of viruses including ChiVMV (Banerjee et al 2014) in Meghalaya and ChiLCV (Baruah et al 2016) in Assam. Talukdar et al (2015Talukdar et al ( , 2017 reported the viral disease incidence on Bhutjolokia in Assam based on DASELISA to be 52%, 52% and 42% for Cucumovirus, Potyvirus and Tospovirus respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Different researches have shown over time that the crop is susceptible to different viruses which include Cucumber mosaic virus (CMV), Potato virus Y (PVY) (Talukdar et al, 2015;Baruah et al, 2016), Tomato Spotted Wilt Virus (TSWV) (Talukdar et al, 2015), Chilli leaf curl virus (ChLCV) ( Talukdar et al, 2015;Baruah et al, 2016) and Groundnut Bud Necrosis Virus (GBNV) (Baruah et al, 2016). Bhut jolokia has also been found to be susceptible to Chilliveinal mottle virus as reported from Meghalaya (Sanabam et al, 2018;Banerjee et al, 2014). The plants are at times infected by a single virus or collectively by different viruses thereby forming a viral complex (Baruah et al, 2016) which reduces the production and productivity to greater extent.…”
Section: Introductionmentioning
confidence: 96%